PROBLEMS OF INHERITANCE OF INTELLECTUAL RIGHTS TO THE RESULTS OF CREATIVE ACTIVITY AND EQUIVALENT OBJECTS - Marina Melnikova; Viktoriia Savina (Гуманитарные и юридические исследования)
In connection with the special nature of intellectual rights to the results of creative activity and objects equated to them, there are certain features of their transition in the order of inheritance, as well as registration of the rights of heirs, not reflected in the norms of part three of the Civil Code of the Russian Federation. Section V of the Civil Code of the Russian Federation is devoted to detailed regulation of general provisions on inheritance, grounds for inheritance, inheritance, and inheritance of certain types of property. Special rules on the inheritance of exclusive rights to various results of intellectual activity are included in the relevant chapters of Part Four of the Civil Code of the Russian Federation, as well as regulated by other normative legal acts adopted in accordance with it. The article examines the peculiarities of inheritance of exclusive rights arising in relation to various results of intellectual activity - objects of copyright and related rights, patent law and the means of individualization of goods, works, services and enterprises that are granted legal protection equated to them. Personal non-property rights are inextricably linked with the personality of the rightholder, which is why they are inalienable and ineffable in other ways. The transfer of these rights to other persons, including, by way of inheritance, is not allowed. The question of how to confirm the testator's exclusive right to the results of intellectual activity and objects equated to them was also investigated. The legal regime specified in Art. 1225 of the Civil Code of the RF objects is significantly different, therefore, the composition of documents confirming the existence of rights to them has sig-niicant differences as well. The procedure for the transfer of certain intellectual rights by inheritance and its design is closely related to the problem of confirming the existence of these rights in a particular person. Therefore, when entering into the composition of the inheritance of intellectual rights, obtaining a certificate of the right to inheritance, as a rule, is necessary. It was concluded that the existence of rules on the inheritance of intellectual property rights in Chapter 65 of the Civil Code of the Russian Federation on the inheritance of certain types of property would make the procedure for registering the rights of heirs of exclusive rights much simpler.